(untitled) (Editora Impacto Científico, 2025)
This study aimed to present and discuss the concept, objectives, and importance of Dietetic Technique as a foundation for quality management and food safety in Food and Nutrition Units (FNUs). The Dietetic Technique, based on applied sciences, studies the physical-chemical and sensory transformations of food, aiming for nutritional, sanitary, and economic optimization. The development detailed the discipline’s objectives and highlighted the Food Preparation Technical Sheet (FTP) as the central management tool. The FTP standardizes recipes by integrating loss and yield calculations (Correction Factor and Conversion Indicator), which is crucial for cost control, menu planning, and the replicability of sensory characteristics. It is concluded that the mastery of Dietetic Technique, materialized through the FTP, is a fundamental competence for the nutritionist to ensure consistency in quality standards, cost control, and food safety in FNUs, converting theory into efficient operational practice. DOI: https://doi.org/10.56238/edimpacto2025.090-028